Conditionally dynamic analysis of the centrifugal compressor operation in the aggregate recirculation line - A. D. Vanyashov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The procedure for conditionally dynamic (quasi-dynamic) hydraulic and thermal calculation of recirculation lines of compressor stations has been developed. As an example, the solution to the problem of reconstruction of the linear compressor station of the main gas pipeline is considered. Using the developed methodology, options for upgrading the existing recirculation line in order to increase its throughput are proposed. The gas temperature change in the recirculation line is analyzed due to various factors (heat exchange with soil, throttling) at the starting modes of constant and variable rotations of the compressor rotor. The analysis of the change in the recirculation cycle time and the rate of temperature growth at the compressor inlet per unit time is performed.